The Impact of Capital Structure on Islamic Banks Performance: Evidence from Pakistan - ATTA ULLAH; MUHAMMAD ILYAS; IHTESHAM KHAN; MUHAMMAD TAHIR KHAN (Journal of Business & Tourism, 2015)
This study investigate the impact of capital structure on the Islamic banks performance during 2008-2013. Selected a sample of 5 Islamic banks on the basis of availability of data. From the findings of the study demonstrate that the impact of capital structure and size is positive and significant on Islamic banks performance. However, Assets Growth is negatively and statistically non-significantly associated with banks performance.